2016
DOI: 10.1016/j.jstrokecerebrovasdis.2016.03.041
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-Radiological Characteristics and Pathological Diagnosis of Cerebral Amyloid Angiopathy-Related Intracerebral Hemorrhage

Abstract: Objective: We aim to clarify the clinico-radiological characteristics of cerebral amyloid angiopathy-related intracerebral hemorrhage and to investigate the efficacy of pathological diagnosis using biopsy specimens. Method: We retrospectively reviewed 253 consecutive patients with cortico-subcortical hemorrhage who had been admitted to Aizawa Hospital between January 2006 and July 2013. We had performed craniotomy and hematoma evacuation in 48 patients, as well as biopsy of the evacuated hematoma, cerebral par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 50 publications
1
19
0
1
Order By: Relevance
“…Our search strategies identified 1,715 articles of which 22 (one cross-sectional study with controls [10] and 21 case series without controls [11–31]) described CT features of CAA-associated lobar or cerebellar ICH in 297 adults, two studies described MRI features [5,32] in 81 adults and one cross-sectional study [33] described both CT and MRI features in 22 adults (Fig 1). There were no PET studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our search strategies identified 1,715 articles of which 22 (one cross-sectional study with controls [10] and 21 case series without controls [11–31]) described CT features of CAA-associated lobar or cerebellar ICH in 297 adults, two studies described MRI features [5,32] in 81 adults and one cross-sectional study [33] described both CT and MRI features in 22 adults (Fig 1). There were no PET studies.…”
Section: Resultsmentioning
confidence: 99%
“…Of the two retrospective hospital-based cross-sectional studies using CT,[10,33] one included 41 cases [10] and the other 22 cases. [33] Both had a high risk of bias owing to inclusion of selected cases, potential misclassification since not all participants received the same reference standard and an unknown time interval between the index test (brain imaging) and the reference standard (histopathological diagnosis).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One previous study showed that lobar CMBs were found most frequently in the temporo‐occipital lobes in patients with hypertension‐related intracerebral hemorrhage (ICH), while they were more frequently found in the parietal lobe in patients with CAA‐related ICH (Lee et al., 2007). Another study with patients with cortico‐subcortical hemorrhage showed that lobar CMBs were most numerous in the parietal lobe in patients with CAA pathology (Doden et al., 2016). A hospital‐based study with patients undergoing MRI screening for neurological symptoms revealed that hypertension had a significant association with CMBs in the posterior cerebral artery area (Jia, Mohammed, Qiu, Hong, & Shi, 2014).…”
Section: Discussionmentioning
confidence: 99%